PENGARUH SDM PETERNAK SAPI PERAH TERHADAP PEMBANGUNAN PETERNAKAN BERKELANJUTAN - Muhammad Alif Nur Kahfi; Amam Amam; Supardi Rusdiana; Nakhma’ussolikhah Nakhma’ussolikhah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Human Resources (HR) of dairy farmers is a potential value owned by farmers for the sustainability of their livestock farming business. HR has several indicators that can be measured and cannot be measured, based on their nature, they can change according to their conditions. This study aims to examine the influence of dairy farmers' human resources on sustainable livestock farming development. The research variables consisted of human resources of farmers (X), the ecological dimension (Y1), the economical dimension (Y2), the social and cultural dimension (Y3), the institutional dimension (Y4), and the technological dimension (Y5). The research was conducted at KUB (Joint Business Group) Tirtasari Kresna Gemilang, Malang District. Data analysis using by SPSS 26.0 method. The results showed that the economical dimension was positively and significantly influenced by the HR of dairy farmers by 0.104, the social and cultural dimensions was positively and significantly influenced by the HR of dairy farmers by 0.205, the institutional dimension was positively and significantly influenced by the HR of dairy farmers by 0.203, and the technological dimension was positively and significantly influenced by the HR of dairy farmers by 0.247. The conclusion of this study is that the human resources of dairy farmers have an effect on sustainable livestock farming development, especially the economical, social and cultural, institutional, and technological.